PH-induced conformational changes in histamine in the solid state - Kanchanok Kodchakorn (2019)
© 2019 The Royal Society of Chemistry. Histamine is one of the most basic biogenic amino-compounds, which is composed of imidazole and a flexible ethylamine side chain moiety. Histamine is known to take the form of various types of cations, free base, monocation and dication form, where its conformational change is highly sensitively to the pH conditions. The details of these changes are still controversial due to a lack of detailed information on its crystal structures. Thus, in this study, the molecular packing structures of histidine at various pH were analyzed via X-ray diffraction in combination with vibrational spectroscopy and energy calculations. A variety of molecular conformations including the tautomeric phenomenon was found to be intimately related with intra- and intermolecular hydrogen bonds. The role of the hydrogen bonds was studied also to check the possibility of high proton conductivity of histamine, as predicted by computer simulation. Consequently, the thus-predicted proton conductivity was confirmed for the first time experimentally. During the heating process, the conductivity showed the relatively high maximum value of 10-4 S cm-1 at around 60 °C, which is related to the effective proton transfer between the amino NH group of one histamine unit and the imidazole ring of another.